Lumbar Plexus Block as an Effective Alternative to Subarachnoid Block for Intertrochanteric Hip Fracture Surgeries in the Elderly - Ahamed, Z. Aejaz (Anesth Essays Res, 2019)
BACKGROUND AND AIMS: Elderly patients with hip fractures pose a medical challenge for the anesthesiologist and are often associated with a high incidence of perioperative morbidity and mortality. We aimed to compare the efficacy of lumbar plexus block (LPB) with subarachnoid block (SAB) in elderly patients undergoing closed reduction and internal fixation for hip fractures. METHODS: In this observational study, 50 patients with femoral intertrochanteric fracture were divided into LPB group and SAB group of 25 each by convenient sampling. Patients in the LPB group were given 20–25 ml of 0.5% bupivacaine to block the ipsilateral lumbar plexus with nerve stimulator assistance, whereas the patients in the SAB group received 0.5% bupivacaine intrathecally. Student's t-test was used for comparing the time for performing block, the time to achieving block, the time to the first request for analgesia, and the hemodynamic variables. RESULTS: Lumbar plexus blockade took a longer time for performing and achieving block (P < 0.001). The time for the first request for analgesia was significantly longer in the LPB group (P < 0.001). A statistically significant reduction in blood pressures was noted in the SAB group. CONCLUSIONS: Lumbar plexus blockade offered more stable intraoperative hemodynamics and longer duration of postoperative analgesia in elderly patients undergoing hip fracture surgery.